Perbandingan Penambahan Air Tebu (Saccharum officinarum) dengan Tuak Manis (Arenga pinnata) sebagai Pengganti Gula terhadap Kualitas Nata De Coco - Mustamin, Mustamin; Sanderia, Iwan (Biocaster : Jurnal Kajian Biologi, 2022)
Nata is a gel-like material (agar) that floats on a medium containing sugar and acid formed by the microorganism Acetobacter xylinum. This study aims to compare the addition of sugarcane juice (Saccharum officinarum) with palm wine (Arenga pinnata) as a sugar substitute on the quality of Nata de Coco. The population in this study were all (Saccaharum officinarum) and (Arenga pinnata) in open land. This type of pure experimental research using Completely Randomized Design (CRD) seven treatments and four replications. Measurable parameters in the form of texture, color, and taste were assessed by means of organoleptic tests. The results show that Nata de Coco using coconut water as the basic ingredient (A) is better than that using sugar cane juice and palm wine with an average total texture of 3.3, color 2.76, and taste 3.12. Then the concentration of sugarcane juice with treatment of 75% sugarcane juice + 25% coconut water (B), is better than the concentration of sugarcane juice and palm wine (C,D,E,F,G). The data obtained were then analyzed using the Analysis of Variance (ANOVA) significant level 5%. The quality of Nata de Coco which uses a mixture of sugarcane juice concentration is better than that of using sweet palm wine.